The Role of Human Resource Information System in Achieving Organizational Excellence - Mohammed, Blesa Ibrahim (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
In highly constant requirement for development competitive environments, there is a need for more comprehensive approaches to achieve sustainable success. This referred on the one hand to the need for an increased participation in the process for change and, on the other, to a more intensive discussion on which method of work organization might be the most productive. Therefore, more holistic concepts are needed in terms of the relationship between human resource management and organizational excellences. Based on the above, this study came to investigate both relationships and impacts of human resource management and organizational excellence among staff in selected private hospitals in the Kurdistan Region Iraq. Methodologically, the quantitative method for data collection was chosen by using a questionnaire survey for sample of 35 respondents. Findings of the study described in a broader context the relationship between human resource management organizational excellence and providing continual learning opportunities are found to have a greater impact on employees’ welfare and increased efficiency of hospital staff in line with contemporary technological development. Based on findings, the study recommended hospitals management to necessity available the HRIS effectively if they wanted to adapt changes more rapidly and to decision-making needs and also if they wanted to enable business planning to be combined with excellence for companies.